HIDUP MANUSIA DI DUNIA KONVERGEN KE f (X) = 0 - Nitta Puspitasari (Institut Pendidikan Indonesia, 2012)
Abstract Mathematics is a discipline that all the concepts, principles, theorems, axioms, rules.It can stand alone or can be connected to the field, the other disciplines. Because mathematics is the queen of sciences. Mathematics is not only connected to other disciplines, but also there is a connection with everyday life. Mathematical concepts with everyday life is a human life. Human life on earth is temporary given time only, whether the people life could not be judge by any one. Thus, analogous to the way of life of each human being is considered as the line function and then each man eventually leading to death or converge to zero in a line function of real numbers, if this function is approaching to zero, its means that one day the peoplelife has ended.